THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE TEAM ASSISTED INDIVIDUALIZATION (TAI) USING CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH ON MATHEMATICAL PROBLEM SOLVING ABILITY GRADE VIII SMP NEGERI 1 BLADO-BATANG ON THE SUBJECT OF THE CIRCLES - Prima Wijaya; Hartono . (Jurnal Pedagogi Matematika, 2017)
This  research  aims  to  analyze  whether  the  cooperative  learning  model  type  Team  Assisted Individualization  (TAI)  and  Contextual  approach  to  Teaching  and  Learning  (CTL)  is  more  effective than the conventional learning model , in terms of the ability of problem solving math grade VIII SMP Negeri  1  Blado  academic  year  2015/2016  on  the  subject  of  the  circle.  This  research  is  the  research experiments using a pretest post test design with two classes, one class as a class experiment and the other as a control class. The population of this research is the whole grade VIII SMP Negeri 1 Blado, and the samples are all the students from class as a class experiment VIIIC provided learning by using cooperative approach with the  contextual  approach  type  of  TAI,  and  all  the  students  of  class  VIII  E  as  control  classes  provided learning by using conventional approaches. Hypothesis testing methods used are independent sample t-test .Based on the analysis of data obtained conclusions the average gain score grade experiment higher significantly than the average gain score class control. This means that the results showed models of cooperative  learning-type  Team  Assisted  Individualization  (TAI)  and  Contextual  approach  to Teaching and Learning (CTL) is more effective than the conventional learning model in mathematical problem solving ability of JUNIOR HIGH SCHOOL students ' views of student learning outcomes.Keyword :The Effectiveness, Cooperative Type Team Assisted Individualization (TAI), Contextual Approach To Teaching And Learning (CTL), Problem Solving